Debt-for-Nature Swaps in Action: Two Case Studies in Peru - Catherine Kilbane. Gockel; Leslie C. Gray (Ecology and Society, 2011)
Debt-for-nature swaps are a major source of global funding for nature conservation and have been touted as a win-win solution to the problem of how to finance conservation. This paper examines how the United States' debt-for-nature-swap program, the Tropical Forest Conservation Act, works in the field. We provide an introduction to the technical aspects of the debt-for-nature swap mechanism, then describe how the program operates on the ground, using the United States-Peru swap as an example. We focus on two case studies that are largely representative of the Tropical Forest Conservation Act's work in Peru: 1) ProNaturaleza's project in the Pacaya Samiria National Reserve, and 2) five distinct projects centered around reducing illegal logging in and around Alto Purús National Park. We explore the range of programs financed through swaps, as well as whether debt-for-nature swap projects meet their goals of strengthening civil society and increasing local capacity. We also discuss the efficacy of debt-for-nature swap monitoring, which tends to privilege fiscal evaluations of area protected over direct conservation outcomes. Although Tropical Forest Conservation Act projects may well have conservation effects, the current methods of measuring success do not reflect the types of conservation impacts of Tropical Forest Conservation Act projects.